Variations in exposure to carcinogens among shift workers and non-shift workers - El-Zaemey, Sonia; Carey, Renee (John Wiley & Sons, Inc., 2019)
© 2019 Wiley Periodicals, Inc. Background: There is limited information on whether the prevalence of exposure to workplace carcinogens varies among shift workers and non-shift workers. Methods: This analysis used data from the Australian Work Exposures Study-Cancer, a telephone survey which examined exposure to carcinogens in the workplace. Workers were classified as shift workers if they indicated that their usual roster ever included work between the hours of midnight and 5 am. Modified Poisson regression was used to estimate the adjusted prevalence ratios (aPRs) and 95% confidence internals (CIs). Results: Among the 5425 workers, 6.88% reported being exposed to shift work. Overall, shift workers were more likely to be exposed to any carcinogen (aPR = 1.16; 95% 1.06-1.26) and to specific carcinogens such as asbestos (aPR = 1.93; 95% 1.33-2.83) than non-shift workers. Conclusions: Our study shows that there are differences in exposure to carcinogenic agents among shift and non-shift workers, and so there is a need for prevention programs in order to reduce these discrepancies.